The poem's passion in Herberto Helder - Carvalho, João Pedro (2021)
This essay analyses love in Herberto Helder’s poetry, and its erotic conception of the poem: transporting the notion of penetration and fusion to a theory of writing and reading. The love poem defines itself as a violent reconstruction of the loved one, as creation of the muse that inspires writing, in a masturbatory cycle. This removal of the Other is the impossibility of reading, and the incessant incitation to the reader, which will never fully read the poem, and, as such, can continue to read it again and again, continuing to be dominated by this total instant of writing/reading.